The bidual of r-algebras - Yilmaz, R. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We prove that the order continuous bidual of an Archimedean r-algebra is a Dedekind complete r-algebra with respect to the Arens multiplications.